(untitled) (Revista Direito em Debate, 2021)
This paper presents a possibility of adapting civil procedural jurisdiction to modernity. Through a theoretical study, we tried to demonstrate the ideological incongruities in the Brazilian civil procedural law as opposed to the emergence of new rights in the 21st century. In spite of recent legislative reformulations, the current procedural model brings together individualistic, patrimonialist and liberal values, with a clear belief in an ordinarized rite as the necessary way to produce a coherent decision. On the other hand, there are renewal waves as a proposed set to effect access to justice within the legal system. The purpose of the question to be raised in this work is that the objective of all movements of access to justice is to humanize the procedural mechanism, in addition to meeting the wishes of the Democratic Rule of Law and seeking to extinguish methods that hinder access to the population. What can be seen, therefore, is the need to improve such a jurisdictional system, with the elaboration of summarized and democratized procedures. The work is divided into two chapters, dealing respectively with: (i) the diagnosis of the state of the art of the Brazilian civil process and the renewal waves of Mauro Cappelletti and Bryant Garth; (ii) the paths to the protagonism of procedural jurisdiction through such waves. Emphasizing, in this work, that the access to justice is not only the search for mechanisms of provocation or exercise of the right of action, but also of a fast, effective and materially compatible judicial protection with the right questioned in court.